Immobility and COVID-19: comparing mobility reduction among socio-demographic groups in a large German city during the pandemic - Leonie Tuitjer; Kerstin J. Schaefer (Transportation, 2023)
The COVID-19 pandemic and the public health measures imposed to tackle the spread of the virus have changed the everyday life and severely reduced the mobility of many. In this paper, we investigate the relationship between changed transport behavior and complex socio-demographic groups. Drawing on a survey on mobility and transport use during the pandemic for the Hanover region (Germany), we find three distinct clusters in our data related to changed mobility behavior: (1) people with no change in transport behavior, (2) people heavily reducing public transport use in the inner city, and (3) people reducing public transport use for their commute. In a second step, we use logistic regression models to understand the socio demographic factors determining each of these change patterns. The results show that women and younger participants were more likely to experience an impact on their travel behavior as well as reducing the use of inner-city public transport, while the reduction of commuter transport seems to be mostly homogeneous once controlled for teleworking. We also find a complex interplay between gender and other socio-demographic factors, especially caring responsibilities for children and student status, to have shaped the reported extent of mobility reduction. We show that we need to think about socio-demographic variables in a more complex way instead of perceiving of them as stand-alone variables. Our analysis hence helps to uncover the complex reality of mobility reduction during the pandemic, providing deeper insights into the (im)mobile reality of people's lives in times of COVID-19.Kindly check and confirm inserted city name are correctly identified.Yes, the city name is Hanover and thus corretly identified~
Keywords: 380; COVID-19; Socio-demographic groups; (im)mobility; Transport behavior; Cluster analysis; Hanover region (Germany)